An essay on man an introduction to a philosophy of human culture - Cassirer, Ernst, 1874-1945 (Yale University Press, 2021)
One of the twentieth century's greatest philosophers presents the results of his lifetime study of man's cultural achievements An Essay on Man is an original synthesis of contemporary knowledge, a unique interpretation of the intellectual crisis of our time, and a brilliant vindication of man's ability to resolve human problems by the courageous use of his mind. In a new introduction Peter E. Gordon situates the book among Cassirer's greater body of work, and looks at why his ""hymn to humanity in an inhuman age"" still resonates with readers today. ""The best-balanced and most mature expres